Oral health KAP and their association with OHRQoL among type 2 diabetic patients in the West Bank, Palestine: a cross-sectional study - Wahbeh, Iman; Enairat, Aesha L. E.; Hemieid, Ihab; Amro, Mahmoud; Abueed, Malak; Hirzallah, Yazan Najem; Kateeb, Elham (Frontiers in Oral Health, 2025)
ObjectivesThis study aimed to assess the impact of knowledge, attitudes, and practices (KAP) related to oral health on oral health-related quality of life (OHRQoL) among patients with type 2 diabetes mellitus (T2DM).MethodsA cross-sectional study was conducted from July 2023 to July 2024 in primary healthcare centers in the West Bank, using cluster sampling to select participants from three geographic regions A convenience sample was drawn from participants aged 40 years and older who were diagnosed with (T2DM). A structured validated Arabic questionnaire was employed to collect data on socio-demographic characteristics, oral health knowledge, attitudes, practices, and OHRQoL, using validated scales such as the OHIP-14.ResultsThe results showed that the mean OHRQoL score was 17.84 ± 11.65 (range 0–50), the primary domains negatively impacting participants' oral health-related quality of life were psychological discomfort, social disability, and handicap. Key oral health problems reported included dry mouth (62.2%), tooth loss (48.6%), and caries (46.1%). Knowledge scores averaged 6.53 ± 2.07 (range 1–10) attitudes scores were 4.88 ± 1.65 (range 0–6), and practices scores were 1.99 ± 1.02 (range 0–6). Spearman's correlation analysis revealed significant positive correlations between practice and knowledge (ρ = 0.160, P = 0.000), practice and attitude (ρ = 0.171, P = 0.000), and Knowledge and attitude (ρ = 0.238, P = 0.000). In the final model, predicting factors to improve OHRQoL were full-time employment, better income, and positive attitude, while poorer OHRQoL was predicted by pain reason to visit dentist, discussion with a dentist about diabetes and oral complications, poor general health status, poor oral health status, lower educational level, no history of diabetes and long duration of to do HbA1c test.ConclusionThis study highlights that positive attitudes significantly improve OHRQoL in diabetic patients, while poor outcomes relate to socioeconomic and health system barriers. Despite good knowledge, practices remain inadequate. Integrating oral health into diabetes care, improving access, and addressing social determinants are essential for enhancing overall quality of life in this population.